484 CHANGING PRACTICES OF DECISION MAKING REGARDING DO-NOT-ATTEMPT-CARDIOPULMONARY-RESUSCITATION ORDERS AMID THE COVID-19 PANDEMIC. (14th June 2021) - Connellan, D; Diffley, K; McCabe, J; Cotter, A; McGinty, T; Sheehan, G; Ryan, K; Cullen, W; Lambert, J; Callaly, E; Kyne, L
Abstract: Introduction: The COVID-19 pandemic has brought the decision-making process regarding cardiopulmonary resuscitation into focus. This study aims to analyse Do-Not-Attempt CPR (DNACPR) documentation in older hospitalised patients before and during the COVID-19 pandemic. Methods: This was a retrospective repeated cross-sectional study. Data including co-morbidities and resuscitation status was collected on 300 patients with COVID-19 hospitalised from March 1st to May 31 s t 2020. DNACPR documentation rates in patients aged ≥65 years with a diagnosis of COVID-19 were compared to those without COVID-19 admitted during the same period. Pre-COVID-19 pandemic DNACPR documentation rates were also examined. Factors associated with DNACPR order instatement during the first wave of the COVID-19 pandemic were identified. Results: Of 300 COVID-19-positive patients, 28% had a DNACPR order documented during their admission. 50% of DNAR orders were recorded within 24 hours of a positive swab result for SARS-CoV-2. Of 131 patients aged 65 years or over within the cohort admitted with COVID-19, 60.3% had a DNACPR order compared to 25.4% of 130 patients ≥65 without COVID-19 (p < 0.0001). During a comparable time period pre-pandemic, 15.4% of 130 older patients had a DNACPR order in place (p < 0.0001). Independent associations with DNACPR order documentation included increasing age (Odds Ratio [O.R.] 1.12; 95% CI 1.05-1.21); nursing home resident status (O.R. 3.57; 95% CI 1.02-12.50); frailty (O.R. 3.34; 95% CI 1.16-9.61) and chronic renal impairment (O.R. 5.49; 1.34-22.47). The case-fatality-rate of older patients with COVID-19 was 29.8% versus 5.4% without COVID-19. Of older COVID-19-positive patients, 39.2% were referred to palliative care services and 70.2% survived. Conclusion: The COVID-19 pandemic has prompted more widespread and earlier decision-making regarding resuscitation status. Although case-fatality-rates were higher for older hospitalised patients with COVID-19, many older patients survived the illness. Advance care planning should be prioritised in all patients and should remain clinical practice despite the pandemic.